The Roler of The Principal in The Establishment of Student Character in The Era Covid-19 - Wati Lilis; Setiabudi Agung (Journal of Educational Management Research, 2022)
The role of the Principal in strengthening character education (Character Education) plays an important and crucial role because it becomes a policy maker and guide in the implementation of character education in schools. The purpose of this study is to see how the principal carries out his role in character building in the school he leads. This study uses a type of field review research using a qualitative approach, with data collection through; observation, interview and literature study. Then analyze the data, reduce the data, and encode the data. The subject of the research is the principal of the MIN 1 Nagan Raya school. Research Location MIN 1 Nagan Raya (Aceh). Based on the results of the study, it was shown that the school principal gave an example before applying the regulations made. Instilling character values both to students and members in other school environments such as honesty, responsibility, discipline, high social and so on. The principal also considers several things in character building, such as planning, curriculum development, learning management and so on.